PENGARUH MODEL IKRAR TERHADAP HASIL BELAJAR SISWA MTS NURUL SA’ADAH - Riza Mahfidia Putri; Risdiana Chandra Dhewy; Intan Bigita Kusumawati (LPPM STKIP PGRI Sidoarjo, 2021)
In k13 learning, learning used is student-centered learning, students are required to actively develop their own knowledge. This study aims to find out the student learning outcomes in the material to construct a flat side space (cubes and beams) using the IKRAR learning model. IKRAR learning model is a learning model that is in accordance with constructivist understanding where in the learning process students are given a mathematical problem and students are required to be active in constructing the concepts learned. This research was conducted in the 2018/2019 school year at MTS Nurul Sa'adah in class VIII-C with a total of 25 students. The type of research used is quantitative which consists of 2 learning meetings and 1 day meeting to evaluate student learning outcomes. The design used in this study is One Shoot Case Study. Sampling in this study uses Simple Random Sampling. This study uses the instruments of teacher observation sheets, student observation sheets and observation sheets of test questions. The data analysis technique used in this study is the classic assumption test followed by using simple linear regression analysis. On the results of this study t test is obtained t test > t table (4,166> 2,069) so that H0 is rejected. Thus it can be concluded that there is an influence between IKRAR learning models on student learning outcomes.